Antibodies to Coxsackie B viruses in congestive cardiomyopathy. Issue 6 (June 1979) - Cambridge, G; MacArthur, C G; Waterson, A P; Goodwin, J F; Oakley, C M
Abstract : Fifty patients with congestive cardiomyopathy have been studied for evidence of previous Coxsackie B virus infection and compared with age- and sex-matched controls who had been admitted to hospital for investigation of other cardiac diseases. High neutralisation titres (greater than or equal to 1024) to Coxsackie B viruses were more common among the controls. On subdividing the patients according to their length of symptomatic history before study, high titres were more common only in those with a short history (less than or equal to 1 year). High titres were more common when there had been a febrile illness at the onset of symptoms. Endomyocardial biopsies of 18 patients disclosed no evidence of myocarditis, or, in 12 cases, of viral involvement. Although the evidence remains circumstantial, these results support the theory that Coxsackie B viruses may cause congestive cardiomyopathy and encourage further research into the mechanisms of myocardial cell damage by these visuses.